2014
DOI: 10.1083/jcb.201309004
|View full text |Cite
|
Sign up to set email alerts
|

An image-based RNAi screen identifies SH3BP1 as a key effector of Semaphorin 3E–PlexinD1 signaling

Abstract: The RhoGAP protein SH3BP1 mediates Sema3E-induced cell collapse through interaction with PlexinD1 and regulation of Rac1 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…Furthermore, the inhibitory effect of sema3e on b 1 integrin in previous reports (24) may be related to simultaneous inhibition of Rap1 and a 4 b 1 integrin activation (13,26). Small GTPase Rac, which also promotes cell adhesion processes and F-actin polymerization, is inhibited by plexin D1 (32). We also found that sema3e inhibited chemokine-induced Rac activation (Y. Ueda, unpublished observations), which could contribute to cell detachment due to actin collapse.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Furthermore, the inhibitory effect of sema3e on b 1 integrin in previous reports (24) may be related to simultaneous inhibition of Rap1 and a 4 b 1 integrin activation (13,26). Small GTPase Rac, which also promotes cell adhesion processes and F-actin polymerization, is inhibited by plexin D1 (32). We also found that sema3e inhibited chemokine-induced Rac activation (Y. Ueda, unpublished observations), which could contribute to cell detachment due to actin collapse.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies reported rapid cell collapse of endothelial cells in response to sema3e/plexin D1 signals and an associated downregulation of Rac activation (32,33). Rac can directly activate integrins (34) or indirectly strengthen integrin-dependent adhesion via cytoskeletal reorganization and morphological changes, such as cell spreading (35).…”
Section: Constitutively Active Rac Did Not Rescue Sema3e-mediated Detmentioning
confidence: 99%
“…Therefore, RacGAPs are also expected to modulate neuronal morphogenesis and synaptic functions. Indeed, through a reduction of Rac1 activity, the Rac1 GAP SH3BP1 was shown to mediate a morphological collapse of developing neurons (Tata et al, 2014).…”
Section: Control By Signalingmentioning
confidence: 99%
“…Comparing the magnitude of fold change between KLF1 and Nan-KLF1 DEGs shows most DEGs are differentially responsive between sample groups (Figure 3.5A). For example, some known KLF1 target genes, such as Alas2 (Tallack & Perkins, 2010a) and Klf10 (Funnell et al, 2007c), are activated equally (4.4-fold & ~100-fold up-regulated respectively) by KLF1 and Nan-KLF1, while other KLF1 target genes such as Alad (Tata et al, 2014) and Hbb-b1 (Miller & Bieker, 1993) are more responsive to KLF1. Finally a third set of genes, not regulated by KLF1, are responsive to Nan-KLF1; this set includes Dusp7, Sh3bp1 and Zfp36.…”
Section: ________mentioning
confidence: 99%
“…it is an example of a Category IV motif (Figure 3.4A). Sh3bp1 is ectopically activated by Nan-KLF1; it is a RhoGAP protein normally expressed by neural tissues (Figure 3.5C) (Tata et al, 2014). Expression in erythroid cells has not previously been reported and aberrant expression could lead to dysregulated signalling.…”
Section: ________mentioning
confidence: 99%